Twofold π‑Extension of Polyarenes via Double and Triple Radical Alkyne peri-Annulations: Radical Cascades Converging on the Same Aromatic Core - Gonzalez-Rodriguez, Edgar; Abdo, Miguel A; dos Passos Gomes, Gabriel; Ayad, Suliman; White, Frankie D; Tsvetkov, Nikolay P; Hanson, Kenneth; Alabugin, Igor V (Journal of the American Chemical Society, 2020)
A versatile synthetic route to distannyl-substituted polyarenes was developed via double radical peri-annulations. The cyclization precursors were equipped with propargylic OMe traceless directing groups (TDGs) for regioselective Sn-radical attack at the triple bonds. The two peri-annulations converge at a variety of polycyclic cores to yield expanded difunctionalized polycyclic aromatic hydrocarbons (PAHs). This approach can be extended to triple peri-annulations, where annulations are coupled with a radical cascade that connects two preexisting aromatic cores via a formal C–H activation step. The installed Bu3Sn groups serve as chemical handles for further functionalization via direct cross-coupling, iodination, or protodestannylation and increase solubility of the products in organic solvents. Photophysical studies reveal that the Bu3Sn-substituted PAHs are moderately fluorescent, and their protodestannylation results in an up to 10-fold fluorescence quantum yield enhancement. DFT calculations identified the most likely possible mechanism of this complex chemical transformation involving two independent peri-cyclizations at the central core.